2018
DOI: 10.1371/journal.pbio.2005595
|View full text |Cite|
|
Sign up to set email alerts
|

Heterochromatin delays CRISPR-Cas9 mutagenesis but does not influence the outcome of mutagenic DNA repair

Abstract: Genome editing occurs in the context of chromatin, which is heterogeneous in structure and function across the genome. Chromatin heterogeneity is thought to affect genome editing efficiency, but this has been challenging to quantify due to the presence of confounding variables. Here, we develop a method that exploits the allele-specific chromatin status of imprinted genes in order to address this problem in cycling mouse embryonic stem cells (mESCs). Because maternal and paternal alleles of imprinted genes hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 61 publications
7
67
1
Order By: Relevance
“…Interestingly, the performance of ScCas9 nuclease is locus-dependent. It has previously been reported that SpCas9 is sensitive to chromatin state, DNA and/ or histone modifications at the target region (Kallimasioti-Pazi et al, 2018). Therefore, we presume that ScCas9 might be more sensitive than SpCas9 to these factors.…”
mentioning
confidence: 76%
“…Interestingly, the performance of ScCas9 nuclease is locus-dependent. It has previously been reported that SpCas9 is sensitive to chromatin state, DNA and/ or histone modifications at the target region (Kallimasioti-Pazi et al, 2018). Therefore, we presume that ScCas9 might be more sensitive than SpCas9 to these factors.…”
mentioning
confidence: 76%
“…Additional systematic profiling of repair outcomes, in different compartments (e.g. open versus closed chromatin) and in different sequence contexts, will be necessary to understand the magnitude and nature of each of these potential sources of chromatin-mediated bias (33,39)…”
Section: Discussionmentioning
confidence: 99%
“…Programmable prokaryotic nucleases such as Cas9 are widely used for eukaryotic genome and transcriptome manipulation, but it is largely unclear how host cells interface with these foreign enzymes. While several studies have uncovered how histones impede Cas9 target search and binding (Hilton et al, 2015; Horlbeck et al, 2016; Kallimasioti-Pazi et al, 2018; Knight et al, 2015; Yarrington et al, 2018), none have described how proteins responsible for restructuring and remodeling nucleosomes might affect Cas9. We have found that the histone chaperone FACT is required for Cas9 unloading and multi-turnover activity in cell-free extract.…”
Section: Discussionmentioning
confidence: 99%